2019
DOI: 10.1097/md.0000000000015992
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of polymerase chain reaction/acid-fast bacilli in conjunction with computed tomography–guided pleural biopsy in tuberculous pleurisy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…However, the positive rate of single acid-fast staining was not high. Previous studies have reported positive acid-fast staining rates of 57.3-64.9% (Li et al, 2019;Rice et al, 2017). In this study, the sensitivity of acid-fast staining was only 63.52%, meaning the diagnosis of approximately a third of these patients is likely to be missed.…”
Section: Discussioncontrasting
confidence: 54%
“…However, the positive rate of single acid-fast staining was not high. Previous studies have reported positive acid-fast staining rates of 57.3-64.9% (Li et al, 2019;Rice et al, 2017). In this study, the sensitivity of acid-fast staining was only 63.52%, meaning the diagnosis of approximately a third of these patients is likely to be missed.…”
Section: Discussioncontrasting
confidence: 54%
“…It had higher sensitivity than PF smear (8.1-fold), mycobacterial culture (1.7-fold), and Xpert MTB/RIF (2.5-fold), indicating that it was more sensitive than current bacteriological and molecular tests which can provide evidence of M. tuberculosis or its nucleic acids in PF. It has been reported that ultrasound, computed tomography (CT), or thoracoscopy-guided pleural biopsy can improve the diagnosis of pleural TB ( 15 , 45 , 46 ). In this study, we found no significant difference in sensitivity between PF IS 6110 OR IS 1081 -dPCR and pleural biopsy in conjunction with acid-fast bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found no significant difference in sensitivity between PF IS 6110 OR IS 1081 -dPCR and pleural biopsy in conjunction with acid-fast bacilli. However, we think that pleural biopsy combined with molecular biological tests such as digital PCR and Xpert can greatly improve the diagnosis of pleural TB ( 14 , 15 , 46 ). Compared with immunological tests, the sensitivity of PF IS 6110 OR IS 1081- dPCR was significantly lower than that of peripheral blood IGRAs (58.8% versus 91.9%, P < 0.001) and higher than that of TB antibody detection in peripheral blood (60.7% versus 42.9%, P = 0.002) or in PF (71.5% versus 40.4%, P = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…The reported sensitivity of PCR is highly heterogeneous, ranging between 45% and 100%, depending on the method of PCR assay, gold standards and method of biopsy. [9 - 11 , 20 - 22] The conventional PCR studies [20 22] reported higher sensitivity (56 - 100%) than the Xpert MTB/RIF assay studies (30 - 85%). [9 – 11] Most studies obtained pleural tissue by either computed tomography-guided biopsy [22] or thoracoscopic biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…[9 - 11 , 20 - 22] The conventional PCR studies [20 22] reported higher sensitivity (56 - 100%) than the Xpert MTB/RIF assay studies (30 - 85%). [9 – 11] Most studies obtained pleural tissue by either computed tomography-guided biopsy [22] or thoracoscopic biopsy. [10 , 11 , 20] Only one study obtained pleural tissue via closed pleural biopsy.…”
Section: Discussionmentioning
confidence: 99%